(3ajV GdhGgH GdYdi aj LhGH SDGd CHj GdehGgH GdMfHdis - (3EHQGgje Hf MSf Hf TgGH GdOjf GdTgQGfj GdTgQRhQqj GdchQGfj, HQgGf GdOjf,J (B1101 (3g` s
(3ChdgG (B:s
(3GdMeO ddg YdGe GdZjhH CeG HYO agPG eG jSQg Gddg ai GdhbJ LhGHkG dSDGd hQO ef Jbi GdOjf eMeO CHh GdehGgH GdMfHdi s
(3BNQgG (B:s
(3bhd eGdc HbQjfI GdZGjI hHGddg GdJhajb ai GdHOGjI hGdfgGjI hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B35 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B21s
Keywords: (3GdeLGejYs